CORRELATION BETWEEN LEARNING STYLE AND STUDENTS’ ENGLISH ACHIEVEMENT AT HEALTH SCIENCE SCHOOL OF BINA HUSADA PALEMBANG - Hapradespa, Aden (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2016)
The success of a lecture is not only determined by the way a lucterer teach but also, the mostimportant and initial is by how students learn. However, every individual has a different way of learning. Thesame thing happen to college students as well, they have different characteristics that make they learn indifferent ways and styles. Some of them can learn fast when immediately doing some tasks assigned to them,but some others in contrary will feel easier when watching somebody else doing those, or only by listeningthe explanation given. Can be assumed, in learning process one has different tendencies toward another.This research had an intention to know the learning style of the students in a purpose to find out isthere any correlation between students‟ learning style and their English achievement. This research was aquantitative study by using correlational approach with taking population of 3rd semester students of PublicHeatlh Study Program in academic year of 2013/2014. Samples were 100 students taken by randomsampling. Analisys of data was done by examining the correlation value of learning styles towards students‟English achievement with using SPSS version 16.0 computer program.The result showed that there was a positive significant correlation between students‟ visual learningstyle and English achievement that was 33.5%, meanwhile a positive significant correlation also was showedbetween students‟ auditory learning style and English achievement that was 34.9%, and the biggest positivesignificant correlation score found in correlation between kinesthetic learning style and English achievementthat was 40.2%. These numbers indicated that a lecturer while giving an English lecture to his studentsshould take a priority on kinesthetic approach because it can develop students‟ enthusiasm and to get easierto understand the material given and at last can improve their English achievement.For other researchers, because learning style is a unique quality within every students, so they candevelop a special teaching model based on the uniqueness of every students in class.